Association Between Dyadic Coping and Quality of Life in Breast Cancer Patients and Their Spouses: An Actor-partner Interdependence Mediation Model - Wei Chen; Hui Li; Jian-Zheng Cai; Nan Qin (Asian Nursing Research, 2024)
Summary: Purpose: This study aims to examine the relationship between dyadic coping (DC), intimate relationship, and quality of life (QOL), and to explore the mediating role of intimate relationship in patients with breast cancer (BC) and their spouses from a dyadic perspective. Methods: A cross-sectional design was used in this present study, and 205 dyads of BC patients and their spouses who completed a sociodemographic and clinical questionnaire and self-reported measures assessing their DC, intimate relationship, and QOL were recruited. The actor-partner interdependence mediation model (APIMeM) was adopted for dyadic distinguished data analysis. The paired t-test, Pearson's correlation coefficients, and the structural equation model were employed for data analysis by using SPSS 22.0 and Amos 24.0. Results: The current study revealed that, for BC patients and their spouses, intimate relationship mediates completely the actor effect of DC on QOL. That is to say, DC was positively related to intimate relationship and then improved QOL. It was interesting to find that, for both patients and their spouses, the intimate relationship could exert a partner-actor complete mediation effect between DC and QOL. Conclusions: The DC perceived by both BC patients and their spouses has significant actor effects on QOL by improving the level of an intimate relationship. Furthermore, intimate relationship has significant actor-actor and partner-actor complete mediation effects for both patients and their spouses. Given the vital role of patient-spouse dyads, nursing staff should take patients’ spouses into account when conducting related psychosocial interventions aiming to improve the QOL of BC patients and their spouses.